Eficácia da instilação de células da linhagem MB49 e gel polimérico termorreversível na imunização contra o carcinoma urotelial de bexiga - Santana, Jhonne Pedro Pedott (Universidade Federal de São Carlos, 2020)
Among the various types of malignant neoplasms, those originating in the bladder can be considered highly impactful due to their prevalence and high recurrence rates, demonstrating the importance of studies involving new therapeutic possibilities. The MB49 cell line is one of the most used for the study of bladder cancer, through its urinary bladder implantation in murine models of tumor induction. Studies have shown that heat shock proteins, such as mortalin, are vital for resistance to the treatment of neoplasms and are present in all processes associated with carcinogenesis. However, there are still not many studies focused on the use of mortalin as a therapeutic target in urothelial bladder carcinoma. Heat shock proteins are also known to play an important role as mediators of immunogenicity. Activating the immune system for therapeutic benefit has long been a goal in immunology, especially in cancer treatment. Antitumor immunotherapy is a promising treatment against several types of cancer, however the low immunogenicity of vaccines remains a limiting factor in this area. Thus, research involving the investigation of the association of these vaccines with immunogenic adjuvants, such as chitosan, is of great relevance for the study of cancer. This thesis aims to: evaluate the pattern of protein expression of mortalin in tumor bladder tissues, using a western blot assay; the investigation of its inhibition effects with MKT-077 on the viability, apoptosis and necrosis of MB49 cells, through viability tests with resazurin and fluorescence; the establishment of a new murine model for the induction of urothelial bladder carcinoma using a thermoreversible polymeric gel (TPG), composed of chitosan and poloxamer; and the identification of the induction of systemic anti-tumor immune response, through a splenocyte cytotoxicity assay, after intravesical inoculation of TPG and MB49 cells. Female mice of the C57BL/6 strain were obtained and used in intravesical tumor cell inoculation procedures. It was observed that mortalin is overexpressed in tumor bladder samples. After the inhibition of mortalin, there was an irreversible reduction in the viability of MB49 cells, promoting an increase in the rates of apoptosis and necrosis in these cells. Antitumor immunotherapy using MB49 cells embedded in a TPG matrix was able to stimulate systemic immune response and affect the development of bladder urothelial carcinoma in an orthotopic and syngeneic murine model.
Efficacy of instillation of MB49 cells and thermoreversible polymeric gel in urothelial bladder carcinoma immunization
Keywords: Câncer de Bexiga; Imunoterapia; Mortalina; Bladder Cancer; Immunotherapy; Mortalin; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::IMUNOLOGIA